2009
DOI: 10.1007/s12539-009-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Kohonen maps for solving the classification puzzle in AGC kinase protein sequences

Abstract: Availability of enormous number of sequences in public domain databases warrants the need for effective tools for clustering and classification of such data. AGC protein kinase family is known to contain many enzymes involved in important cellular processes. In the present study, 21 important physicochemical parameters were calculated for 115 sequences of AGC kinase family belonging to mouse and human. Kohonen maps, also known as Self Organizing Maps (SOM) were employed for the identification of clusters of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Medical informatics, the application of Information Technology techniques involves examination of patient records and reports and through analysing of huge amounts of such data; complex interactions and correlation in it is revealed [42][43][44][45][46]. Practical application is observed in areas such as oncology, liver pathology, thyroid disease diagnosis, rheumatology, dermatology, cardiology, neuropsychology, gynaecology and perinatology [47][48][49][50]. Medical data is now facing serious setbacks as we still have not been able to come up with statistical methods capable of dealing with noisy and missing data [51][52][53].…”
Section: Ai Applicationsmentioning
confidence: 99%
“…Medical informatics, the application of Information Technology techniques involves examination of patient records and reports and through analysing of huge amounts of such data; complex interactions and correlation in it is revealed [42][43][44][45][46]. Practical application is observed in areas such as oncology, liver pathology, thyroid disease diagnosis, rheumatology, dermatology, cardiology, neuropsychology, gynaecology and perinatology [47][48][49][50]. Medical data is now facing serious setbacks as we still have not been able to come up with statistical methods capable of dealing with noisy and missing data [51][52][53].…”
Section: Ai Applicationsmentioning
confidence: 99%
“…In order to cluster the resulting, spatially assigned sliding-window dataset, a SOFM neural network using Gaussian distance functions was used. SOFM networks have been successfully used to find patterns in high-dimensional and large datasets [33][34][35][36].…”
Section: Finding Regional Trends In Phase Shiftmentioning
confidence: 99%
“…In the present study we have adopted an intelligent method dependent approach for classification and clustering the bacterial Pyruvate Dehydrogenase protein sequences according to their genera based on their physicochemical properties [14,15]. Similar kind of studies we have reported in the recent past [16,17,18]. …”
Section: Introductionmentioning
confidence: 97%